Speech Acts across Cultures: Teaching Compliment Exchanges - Stoian, Claudia E. (East-West cultural passage, 2020)
Speaking a foreign language implies more than knowing its vocabulary and grammar. As such, teachers of foreign languages should keep this in mind and consider also other aspects than the ones mentioned. Attention should be paid to pragmatics and cultural issues, among others. The present essay aims to highlight the importance of raising foreign language students’ awareness of national and international linguistic and cultural behaviours. It describes briefly the field of cross-cultural pragmatics, focusing on speech acts and their culture-sensitive features. Then, it turns to one of the most important types of speech acts, namely compliment exchanges. Taking into consideration the key role played in cross-cultural communication by the appropriateness of compliments and their expected answers, the article proposes several activities to do in class in order to (1) raise students’ awareness regarding the importance of compliments for successful communication, (2) present them the usual patterns, topics, and cultural particularities of compliments, (3) familiarise students with possible communication threats, and (4) provide them with possible strategies to answer compliments. The activities are not restricted to students of foreign languages in general but are recommended also to those studying specialised subjects in foreign languages, such as communication, translation and interpreting.